Bagaimana Teknologi Digital Mendukung Pendidikan Dasar: Pelatihan AI untuk Guru - Andik Prakasa Hadi; Setiyo Adi Nugroho; Rudjiono Rudjiono; Agus Priyadi; Ahmad Zainudin (Pusat Riset dan Inovasi Nasional, 2025)
The advancement of artificial intelligence (AI) has opened new opportunities in education, particularly at the primary level. This article presents the outcomes of an AI training program for early childhood education (PAUD) teachers in Semarang Regency, aimed at enhancing their understanding and skills in integrating technology into teaching and administration. The study employed observations, interviews, post-tests, and focus group discussions. Findings reveal significant improvement in teachers’ abilities to use tools like ChatGPT and Canva, alongside increased confidence in adopting technology. However, infrastructure limitations and lack of post-training support remain key challenges. The study highlights the need for continuous and adaptive training to ensure successful AI integration in education.